2014
DOI: 10.1098/rstb.2013.0578
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect responses of a freshwater food web to a potent synthetic oestrogen

Abstract: Endocrine-disrupting chemicals (EDCs) in municipal effluents directly affect the sexual development and reproductive success of fishes, but indirect effects on invertebrate prey or fish predators through reduced predation or prey availability, respectively, are unknown. At the Experimental Lakes Area in northwestern Ontario, Canada, a long-term, whole-lake experiment was conducted using a before-after-control-impact design to determine both direct and indirect effects of the synthetic oestrogen used in the bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
155
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(161 citation statements)
references
References 54 publications
3
155
0
3
Order By: Relevance
“…Some models have indicated that short-lived, asynchronous spawning fish, such as the fathead minnow, may be more susceptible to population decline compared with longer-lived, seasonal spawning brook trout (Salvelinus fontinalis), following simulated multi-generation exposures to endocrine active chemicals [41]. These findings are consistent with studies on an experimental lake dosed for 3 years with the synthetic oestrogen EE2, which resulted in significant population decline in fathead minnows, but not the longer-lived, demersal white sucker (Catostomus commersonii) [15]. There is also some indication of increasing, heritable susceptibility to EE2 over generations, according to mesocosm studies on fathead minnows [42], and this is supported by laboratory life cycle studies on fathead minnows and zebrafish [43,44].…”
Section: Introduction (A) Environmental Risks Associated With Pharmacsupporting
confidence: 81%
See 2 more Smart Citations
“…Some models have indicated that short-lived, asynchronous spawning fish, such as the fathead minnow, may be more susceptible to population decline compared with longer-lived, seasonal spawning brook trout (Salvelinus fontinalis), following simulated multi-generation exposures to endocrine active chemicals [41]. These findings are consistent with studies on an experimental lake dosed for 3 years with the synthetic oestrogen EE2, which resulted in significant population decline in fathead minnows, but not the longer-lived, demersal white sucker (Catostomus commersonii) [15]. There is also some indication of increasing, heritable susceptibility to EE2 over generations, according to mesocosm studies on fathead minnows [42], and this is supported by laboratory life cycle studies on fathead minnows and zebrafish [43,44].…”
Section: Introduction (A) Environmental Risks Associated With Pharmacsupporting
confidence: 81%
“…Other small fish species, such as the Chinese rare minnow (Gobiocypris rarus) may be even more susceptible to EE2 [45]. It is also possible that longer-term exposures to chemicals, including pharmaceuticals, may eventually become more problematic for longer-lived species with relatively low lifetime fecundity and inflexible lifehistory strategies [38,39] and/or fish species occurring higher in the food chain [15].…”
Section: Introduction (A) Environmental Risks Associated With Pharmacmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted the chronic impacts that certain drugs can have on aquatic organisms, especially fish [1][2][3][4][5][6]. In terrestrial systems, PIE has received less attention, yet one drug has had an acute impact on global population sizes of at least three bird species.…”
Section: Introductionmentioning
confidence: 99%
“…Segner 2011, Shore et al 2014). An example is provided by the experimental lake study of Kidd et al (2007Kidd et al ( , 2012: dosing a Canadian lake over 3 years with about 5 ng L −1 of the pharmaceutical ethinylestradiol did not cause any mortalities among the exposed fish species but caused specific molecular, cellular and physiological changes which eventually inhibited successful recruitment thereby leading to extinction of fish species such as fathead minnow. Interestingly, not all fish species were affected, what appears to be on one hand related to differences of physiological properties among the exposed species, but on the other hand, it relates to indirect effects of the chemical exposure on the food web of the lake.…”
Section: This Special Issue Of Environmental Science and Pollutionmentioning
confidence: 99%